THE RELATION BETWEEN POLITICAL IDEOLOGY AND RADICAL ENVIRONMENTALISM - Aleksandar Matkovic (Srpska Politička Misao)
The aim of this paper is examination of general relationship between political ideology and radical environmental activism, with a special focus on considering the extent of influence and the exact position of the politics in the domain of mentioned eco-activism. Within the first four parts, the general characteristics of radical environmentalism, as well as its relationship with the political left-wing, political right-wing and apolitical/anti-political beliefs are analyzed, while the final part is devoted to discussion and general conclusions. Among other things, it was concluded that the basic ideological dimension of radical eco-activism is based on the idea of biocentrism, as the original environmental and nonpolitical category, while political ideological elements represent secondary and facultative components that can influence the specification of the ideology of a part of eco-activists. At the same time, it was pointed out that the proper perception of such (i.e. secondary) position of political beliefs within the radical eco-activism creates a precondition for understanding heterogeneity and frequent contradictions in the political beliefs of radical eco-activists.